2021
DOI: 10.3390/healthcare9030295
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Failure of Bakri Balloon Tamponade for the Management of Postpartum Haemorrhage. Case Series Study and Systematic Review

Abstract: Background: Postpartum haemorrhage (PPH) is an unpredictable obstetric emergency that requires a multidisciplinary approach. Bakri balloon tamponade (BBT) is recommended when PPH does not respond to medical treatment. Nowadays few published studies have performed a multivariate analysis to determine the variables independently associated with BBT failure. Methods: Our study purpose was to determine the variables independently associated with BBT failure: first, in a large single-centre cohort study between 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…The fact that the success rate after the first embolization is higher than after repeated embolizations (79.2% vs. 66.7%) indicates that the longer it takes to correct the bleeding, the less successful the embolization is. The time factor has been associated with the failure of other obstetric hemorrhage treatments, such as the Bakri balloon [ 13 ]. There have been no studies comparing the effectiveness of repeat embolization versus medical therapy or hysterectomy for persistent bleeding after initial embolization.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the success rate after the first embolization is higher than after repeated embolizations (79.2% vs. 66.7%) indicates that the longer it takes to correct the bleeding, the less successful the embolization is. The time factor has been associated with the failure of other obstetric hemorrhage treatments, such as the Bakri balloon [ 13 ]. There have been no studies comparing the effectiveness of repeat embolization versus medical therapy or hysterectomy for persistent bleeding after initial embolization.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, Wang et al [7] also reported that DIC development is one of the risk factors in the BBT failure. Ruiz Labarta et al [11] found that EBL before insertion was associated with BBT failure. In addition, PAS is associated with life-threatening maternal PPH.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, BBT is effective in the treatment of PPH and has the value of clinical promotion. Factors for BBT failure mainly included pre-pregnancy obesity, maternal age, caesarean delivery, estimated blood loss before BBT insertion, long operation duration, and coagulopathy [11,12]. To reduce massive hemorrhage more effectively, it is necessary to identify the risk factors of BBT failure.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work by Labarta et al risk factors associated with PPH that were found were induction of labour (47.2%), twin pregnancies in 22% and 12% had a previous caesarean section. 8 However, the main cause of PPH was uterine atony in 69%, with retained tissue in 11%. To arrest bleeding, 65% of women required a uterine curettage before insertion of the Bakri balloon.…”
Section: Risk Factors For Pphmentioning
confidence: 99%